2019
DOI: 10.5812/jjm.96513
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Common Respiratory Viruses in Patients with Acute Respiratory Infections Using Multiplex Real-Time RT-PCR

Abstract: Background: Acute respiratory infection (ARI) is caused by human metapneumovirus (HMPV), respiratory syncytial virus type A and B (RSV-A, RSV-B), human parainfluenza viruses 1, 2, and 3 (HPIV-1, HPIV-2, and HPIV-3), influenza viruses A and B (IfV-A, IfV-B), and human coronaviruses (OC43/HKU1, NL63, 229E) worldwide. Objectives: This study was conducted to assess the causative agents of viral ARI among hospitalized adults by real-time PCR. Methods: Clinical nasopharyngeal swabs of 112 patients including 55 (49.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…A recent retrospective analysis of coronavirus detections in respiratory samples across the USA in a three-year period showed that HKU 1 is less common than other coronavirus species; more than 45% of the patients were under 18 years of age; no correlation between different coronavirus species and clinical features was reported (18). An Iranian study among adult patients hospitalized for acute respiratory infection did not find positivity for any of the coronaviruses investigated (HKU 1 included) (19). A Chinese study specifically conducted in Beijing over a period of 4 years on adult (over 14 years) outpatients with respiratory symptoms and normal chest X-rays showed that only 1% had a coronavirus infection (87/ 8396) and only 14 patients (0.2%) were positive for HKU 1.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective analysis of coronavirus detections in respiratory samples across the USA in a three-year period showed that HKU 1 is less common than other coronavirus species; more than 45% of the patients were under 18 years of age; no correlation between different coronavirus species and clinical features was reported (18). An Iranian study among adult patients hospitalized for acute respiratory infection did not find positivity for any of the coronaviruses investigated (HKU 1 included) (19). A Chinese study specifically conducted in Beijing over a period of 4 years on adult (over 14 years) outpatients with respiratory symptoms and normal chest X-rays showed that only 1% had a coronavirus infection (87/ 8396) and only 14 patients (0.2%) were positive for HKU 1.…”
Section: Discussionmentioning
confidence: 99%